(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The Indonesian Throughflow (ITF) is an inter-ocean Pacific-Indian current system that passes Indonesian Seas, such as via the primary path of Makassar Strait to Flores Sea and via the secondary path of Lifamatola Strait to Banda Sea. This study aims to investigate the structure and volume transport estimate of ITF Eastern Flores Sea (Flores) and Northern Banda Sea (Banda) derived from ocean model output of INDESO between 2008 and 2014. Structure of the ITF is analyzied by the average of current component vertically and transport volume estimated by cross-section at Banda and Flores sea. Time-series variability of ITF is analyzed using band-pass filter and continuous wavelet transforms. The results showed that ITF Banda was characterized by flow dominantly towards south while ITF Flores depicted was flowing east along the North of Nusa Tenggara Islands. The vertical structure of ITF flow is intensified at a depth between 50 m and 150 m. The total volume transport estimate over the 7-year period from both ITF paths into the western Banda Sea is about 6.27 Sv (±3.81 Sv), which is a good agreement with previous model studies. Variations of transports ITF in Banda (Flores) is maximum during northwest (southeast) monsoon and minimum during southeast (northwest) monsoon. The variability of the ITF Banda is dominated intra-seasonal (ISV) and semi-annual periods (SAV), while the ITF Flores is annual period (AV).